Pengaruh Produk Dan Harga Karet Rakyat Terhadap Pendapatan Masyarakat Di Desa Tanjung Raman Kota Prabumulih Selatan - Mulyani, Agus; Ilhamsyah; Rosadian, Aprizal; Oktariansyah (Universitas PGRI Palembang, 2023)
ABSTRAK Tujuan penelitian untuk mengetahui produk (X1), harga karet (X2) yang berpengaruh terhadap pendapatan masyarakat (Y) variabel terikat. Populasi adalah seluruh masyarakat di Desa Tanjung Raman sebanayk 200 orang sedangkan teknik pengambilan sampel probabilitas sampel menggunakan rumus Slovin tingkat kesalahan e = 5% diperoleh sampel nya 134 orang. Teknik pengumpulan data adalah kuesioner dan wawancara. Dengan cara menyebar angket dan bertanya secara secara langsung masyarakt di Desa Tanjung Raman Prabumulih Selatan. Pengujian Instrumen yaitu uji validitas instrumen, uji reliabilitas. Metode analisis yaitu uji normalitas data, uji model terdiri uji heteroskedastisitas. uji multikolinieritas, Model Analisis yaitu analisis jalur yang dihitung dengan dua persamaan struktural yaitu persamaan regresi yang menunjukkan hubungan yang dihipotesiskan, uji koefisien untuk melihat tingkat signifikansi masing-masing koefisien regresi menggunakan SPSS. Hasil Penelitian menunjukkan bahwa kedua faktor mempengaruhi pendapatan masyarakat di Desa Tanjung Raman Prabumulih Selatan. Kata kunci: Produk, Harga dan Pendapatan Masayarakat. ABSTRACT Rubber is a plantation that is very helpful and is develoved by the community, especially in Tanjung Raman Village. However, the current proble is that the price of rubber is less stable and tends to decrease, causing many people to suffer from the decline in the price of latex. The purpose of this study was to analyze the influence of rubber farmers, income in the new normal era South Prabumulih in terms of rubber products and prices. In this study using quantitative descrptive research. The researcher understands that this research is only limitedto examining the sources studied in further research. The result of the discussion in this study consist of looking at the current condition of South Sumatra Rubber farmers, especially in South Prabumulih City. The farmers are currently experiencing a very difficult time with the decline in the price of rubber sap.. This impact is because rubber latex in Indonesia, especialy Sumatera, has a quality peiod that is considered below average. So to improve this quality, farmers increase their rubber latex products and avoid cheating taht harms other rubber farmers. Meanwhile, another discussion is the analysisi of the income of rubber farmersduring the new normal period in South Prabumulih, namely that generally people who rely on rubber sap as a support for their lives are stating to experience difficulties and declining economic pressure.Rubber plantations develoved by farmers are generally not privately owned, but only work for people who do own the rubber plantations. To support the family economy, people began to do side jobs to make ends meet, the government,s role in increasing rubber prices was very importand. Various innovations that are able to raise the price of rubber latex are highly anticipated by the people of Prabumulih. In conclusion, cooperation between the government and the community greatly determines the life of the rubber farming solutions to the declining price of rubber sap. Keywords: Product, Price and Community Income.